ISLAMIC MICROFINANCE ACCESS AND SOCIAL COHESION IN THE SURVIVAL OF WOMEN'S MSMEs AMONG ROHINGYA IMMIGRANTS IN BANGLADESH - Uus Ahmad Husaeni; Mohammad Ullah Khan (Universitas Airlangga, 2026)
Micro, small, and medium enterprises (MSMEs) run by women are crucial for supporting the economies of vulnerable communities, including forced immigrant groups in Bangladesh, such as the Rohingya. However, two major barriers to their business sustainability are limited access to financing and a lack of physical collateral. The purpose of this study was to examine how social cohesion and access to Islamic microfinance influence the sustainability of women MSMEs among Rohingya immigrants living in Bangladesh. This study employed a quantitative cross-sectional design. SmartPLS-based Structural Equation Modeling (SEM) was used to analyze data collected from 114 MSMEs owned by Rohingya immigrant women in Chittagong Division. The results indicate that access to Islamic microfinance has a positive and significant effect on the sustainability of women's micro, small, and medium enterprises. Through monitoring mechanisms, shared responsibility, and reduced information asymmetry, social cohesion also proved beneficial and significant for business sustainability. The coefficient of determination indicated that both variables together accounted for 72.2 percent of the variation in the sustainability of women's MSMEs. The results indicate that integrating social and financial capital is a crucial component of the success of women's MSMEs in forced migration and post-conflict contexts. This study provides theoretical and empirical contributions to the literature on Islamic microfinance and women's entrepreneurship. It provides policy implications for creating inclusive and sustainable financing for vulnerable immigrant communities.